2006
DOI: 10.4103/0973-1482.25849
|View full text |Cite
|
Sign up to set email alerts
|

A prospective and randomized study of radiotherapy, sequential chemotherapy radiotherapy and concomitant chemo therapy-radiotherapy in unresectable non small cell carcinoma of the lung

Abstract: Addition of chemotherapy with radiation in unresectable NSCLC improves response rates, time to tumour progression and disease free survival, though the same effect is not translated in overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Similar results were obtained for subgroup analysis of the five Phase-III trials. 15,19,20,21,37 Patterns of failure Pooling data of the initial relapse sites (Figure 2), difference between overall relapses (locoregional or distant) in both groups was statistically significant (OR ¼ 0.82; 95%CI: 0.69-0.97; p ¼ 0.02) in favor of concurrent group. Subset analyses revealed that isolated loco-regional relapses (primary tumor and/or regional nodes) were significantly lower frequent in the concurrent RT-CT than in the sequential arm (OR ¼ 0.68; 95%CI: 0.52-0.87; p ¼ 0.002), while the number of distant (e.g., brain, bone, or liver) relapses (OR ¼ 1.01; 95%CI: 0.79-1.30; p ¼ 0.927) and relapses at both sites (locoregional þ distant) (OR ¼ 0.74; 95%CI: 0.43-1.12; p ¼ 0.267) were similar in the two arms.…”
Section: Progression-free Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were obtained for subgroup analysis of the five Phase-III trials. 15,19,20,21,37 Patterns of failure Pooling data of the initial relapse sites (Figure 2), difference between overall relapses (locoregional or distant) in both groups was statistically significant (OR ¼ 0.82; 95%CI: 0.69-0.97; p ¼ 0.02) in favor of concurrent group. Subset analyses revealed that isolated loco-regional relapses (primary tumor and/or regional nodes) were significantly lower frequent in the concurrent RT-CT than in the sequential arm (OR ¼ 0.68; 95%CI: 0.52-0.87; p ¼ 0.002), while the number of distant (e.g., brain, bone, or liver) relapses (OR ¼ 1.01; 95%CI: 0.79-1.30; p ¼ 0.927) and relapses at both sites (locoregional þ distant) (OR ¼ 0.74; 95%CI: 0.43-1.12; p ¼ 0.267) were similar in the two arms.…”
Section: Progression-free Survivalmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23]37,38 Main characteristics of the 11 trials are described in Table 1. Of the 11 trials, 6 were randomized phase III trials, 15,16,[19][20][21]37 and the remaining 5 were randomized phase II trials. As of August 2009, 10 trials have already been published as full length articles and one was presented at the 2003 Annual Meeting of the ASCO.…”
Section: Trial Flow and Characteristics Of The Eligible Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One trial 56 reported details of co-interventions; however, it was unclear how many patients in each treatment arm had received any of the co-interventions. Two trials 49,51 were reported as 'open' and it was assumed that assessors, administrators and participants were not blinded to treatment; blinding was not stated in the remaining 17 trials.…”
Section: Qualitymentioning
confidence: 99%
“…51 Eighteen trials clearly reported the number of participants randomised. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][61][62][63] All trials reported details of participant comparability at baseline.…”
Section: Qualitymentioning
confidence: 99%